APLIKASI ALTERNATIF MATERIAL BERBASIS VEGAN SEBAGAI PENDUKUNG GERAKAN SUSTAINABILITY FASHION - Enrico Enrico (Universitas Ciputra Surabaya, 2019)
Fashion sustainability using Vegan-based Materials as An Alternative Application.Fashion sustainability is a movement in fashion industry to support our world’s sustainability. Not only wastes generated in fashion and textile industry have negative impacts on the environment, but also its raw materials and how it is manufactured. To support this movement, several methods have been tried, one of them is to replace the conventional textile materials with organic materials. This research will be done using qualitative descriptive method with observation, literature study and case study from several fashion brands which support fashion sustainability movement.